(((Semitism))) : being Jewish in America in the age of Trump - Weisman, Jonathan (St. Martin's Press, 2018)
"A short, literary, powerful contemplation on how Jews are viewed in America since the election of Donald J. Trump, and how we can move forward to fight anti-Semitism. Anti-Semitism has always been present in American culture, but with the rise of the Alt Right and an uptick of threats to Jewish communities since Trump took office, New York Times editor Jonathan Weisman has produced a book that could not be more important or timely. When Weisman was attacked on Twitter by a wave of neo-Nazis and anti-Semites, witnessing tropes such as the Jew as a leftist anarchist; as a rapacious, Wall Street profiteer; and as a money-bags financier orchestrating war for Israel, he stopped to wonder: How has the Jewish experience changed, especially under a leader like Donald Trump? In (((Semitism))), Weisman will explore the disconnect between his own sense of Jewish identity and the expectations of his detractors and supporters. He will delve into the rise of the Alt Right, their roots in older anti-Semitic organizations, the odd ancientness of their grievances...cloaked as they are in contemporary, techy hipsterism...and their aims...to spread hate in a palatable way through a political structure that has so suddenly become tolerant of their views. He will conclude with what we should do next, realizing that vicious as it is, anti-Semitism must be seen through the lens of more pressing threats. He proposes a unification of American Judaism around the defense of self and of others even more vulnerable: the undocumented immigrants, refugees, Muslim Americans, and black activists who have been directly targeted, not just by the tolerated Alt Right, but by the Trump White House itself"...